Analysis of the Effect of Unemployment and Household Consumption on Poverty Through Economic Growth as an Intervening Variable - Wulan Dwi Lusiarani; Muhammad Firmansyah; Stanislaw Flejterski (International Journal of Economics Development Research (IJEDR), 2023)
Poverty is the main problem faced by almost all countries in the world, including Indonesia. Poverty can be overcome by continuing to boost the economic growth rate because economic growth is a projection or reflection of the welfare and prosperity of the people in a country. By writing this article, the author aims to determine how the unemployment rate and household consumption variables influence poverty in Indonesia through economic growth as an intervening variable. The data used in writing this article is secondary data obtained from the Indonesian Central Statistics Agency. The analysis technique used is path analysis. The software used in this research is SPSS. The research results show that the Unemployment Rate (X1) and Household Consumption (X2) directly have a significant effect on Poverty (Y2). In addition, the Unemployment Rate and Household Consumption significantly affect Poverty through Economic Growth (Y1) as intervening variables.